2022
DOI: 10.3389/fmolb.2022.854624
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) Modulates Carotid Atherosclerosis in Metabolic Syndrome

Abstract: Background and Aim: High lipoprotein(a) [Lp(a)] is a well-established cardiovascular (CV) risk factor, but the effect of mildly elevated Lp(a) on CV health is largely unknown. Our aim was to evaluate if Lp(a) is associated with the severity of carotid atherosclerosis (CA) in the specific subset of metabolic syndrome (MetS).Patients and Methods: Subjects with diagnosed MetS and ultrasound-assessed CA were enrolled. Those patients were categorized according to the severity of CA (moderate vs. severe), and the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The Atherothrombosis Intervention in Metabolic Syndrome with Low HDL-C/High Triglycerides: Impact on Global Health Outcomes (AIM-HIGH) study has demonstrated an independent association of elevated Lp(a) with residual cardiovascular risk, atherosclerosis progression and the development of high-risk plaque features in patients with metabolic syndrome [59]. Although similar findings have been replicated subsequently [60], the association of Lp(a) with metabolic syndrome has been controversial. The Maracaibo City Metabolic Syndrome Prevalence Study showed a significant positive association of metabolic syndrome and Lp(a) concentration as well as a progressive increase in Lp(a) concentration as number of components of metabolic syndrome increased.…”
Section: Novel Cardiovascular Risk Factors and Metabolic Syndromementioning
confidence: 99%
“…The Atherothrombosis Intervention in Metabolic Syndrome with Low HDL-C/High Triglycerides: Impact on Global Health Outcomes (AIM-HIGH) study has demonstrated an independent association of elevated Lp(a) with residual cardiovascular risk, atherosclerosis progression and the development of high-risk plaque features in patients with metabolic syndrome [59]. Although similar findings have been replicated subsequently [60], the association of Lp(a) with metabolic syndrome has been controversial. The Maracaibo City Metabolic Syndrome Prevalence Study showed a significant positive association of metabolic syndrome and Lp(a) concentration as well as a progressive increase in Lp(a) concentration as number of components of metabolic syndrome increased.…”
Section: Novel Cardiovascular Risk Factors and Metabolic Syndromementioning
confidence: 99%